2012
DOI: 10.1128/jvi.01101-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Bluetongue Virus Serotype 9: Implications for Serotyping

Abstract: bThe second complete genome of bluetongue virus serotype 9 (BTV-9) is presented in this report. The sequence analysis points to continued circulation in India of a mixed topotype virus apparently belonging to the BTV-9 serotype, and it raises questions about approaches for serotyping bluetongue viruses. Bluetongue virus (BTV) is a 10-segmented double-stranded RNA virus belonging to the genus Orbivirus, family Reoviridae. BTV infects most ruminant species, but the clinical disease is limited to sheep and, to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…The considerable degree of cross neutralization between BTV‐9 and BTV‐5 found in this study (Tables and ), and previously documented by others (Rao et al . ), could explain the perceived existence of BTV‐5 antibodies in host animals in Eastern lineage regions. Our phylogenetic analysis of the relationships between Seg‐2 and Seg‐6 of BTV‐5 isolates showed that these belonged to Western topotype lineages (W‐1/W‐2) whereas for BTV‐9 isolates, both Western and Eastern lineage clades exist for this serotype, involving two Western lineages (W‐1/W‐2) and a single Eastern lineage (E‐1) (Figures a & b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The considerable degree of cross neutralization between BTV‐9 and BTV‐5 found in this study (Tables and ), and previously documented by others (Rao et al . ), could explain the perceived existence of BTV‐5 antibodies in host animals in Eastern lineage regions. Our phylogenetic analysis of the relationships between Seg‐2 and Seg‐6 of BTV‐5 isolates showed that these belonged to Western topotype lineages (W‐1/W‐2) whereas for BTV‐9 isolates, both Western and Eastern lineage clades exist for this serotype, involving two Western lineages (W‐1/W‐2) and a single Eastern lineage (E‐1) (Figures a & b).…”
Section: Discussionmentioning
confidence: 99%
“…Of note was the finding in this study and by others previously (Rao et al ., ; Rao et al . ; Shirafuji et al . ; Maan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six different serotypes of BTV are recognized worldwide and distinct topotypes defined by closely related sequences of each genome segment have been proposed [19]. In India, 23 serotypes of BTV have been reported, identified either by serology or virus isolation, and eight serotypes (BTV-1, -2, -3, -9, -10, -16, -21, and -23) have been isolated from different regions during the last decade [4,5,8,12,17,22,26,28,30,33,36,37].BT is endemic in India. Multiple serotypes of BTV commonly circulate in the same geographical area, and can be isolated from the same flock or even from the same animals.…”
mentioning
confidence: 99%
“…Recently three serotypes (BTV-3, -9, and -21) have been isolated from India [5,17,30,31,37] (http:// www.ainpbt.com/achievement.html). To select different serotypes of BTV for inclusion in polyvalent vaccines, a comprehensive and continuous type-specific sero-prevalence is needed.…”
mentioning
confidence: 99%
“…Till date, 15 BTV serotypes (BTV-1, BTV-2, BTV-3, BTV-4, BTV-5, BTV-6, BTV-9, BTV-10, BTV-12, BTV-16, BTV-17, BTV-18, BTV-21, BTV-23 and BTV-24) have been isolated in India since 2001 Rao et al, 2016;Biswas et al, 2010;Gollapalli et al, 2012;Dadawala et al, 2012;Rao et al, 2012;Himadri et al, 2016). BTV-12 has been isolated and sequenced earlier from Andhra Pradesh, one of the southern states of India in 2011 (Rao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%